Application of Digital Informatics in Precision Prevention, Epidemiology, and Clinicogenomics Research to Advance Precision Healthcare - He, Qiang; Silva, Patrick J.; Ory, Marcia; Wang, Ni; Ramos, Kenneth S. (Yearbook of Medical Informatics, 2024)
Objectives: To summarize recent public health informatics and precision epidemiology developments impacting the healthcare ecosystem. The influence of new technologies and precision approaches in surveillance and management of chronic diseases is high-lighted as areas of clinical practice where digital informatics can markedly improve pop-ulation health.Methods: In this narrative review, we summarized the main themes from research and practice to define disease prevention and public health trends. Publications on public health informatics and precision epidemiology were searched using Google Scholar us-ing the following keywords: “digital informatics”, “precision in prevention”, “precision epi-demiology”, “public health surveillance”, “clinicogenomics” and combinations thereof. In addition, we introduced the principles of a clinicogenomics registry as a case study to empower underrepresented communities and to reduce health disparities.Results: Technology applications such as telehealth and digital information tools fre-quently intertwine with public health informatics and precision epidemiology in efforts to identify and target individuals and populations at risk of disease. There is an urgent need for more investigations and evaluation of the validity and utility of digital platforms, including artificial intelligence (AI) and predictive analytics to advance precision preven-tion and epidemiology. The major precision-based opportunities identified included: (1) the utilization of digital tools, (2) a public health strategic framework, (3) tele-health/telemonitoring tools, (4) digital twins to simulate and optimize care models, (5) clinicogenomics registries, (6) biomarker analyses and omics panels, and (7) mobile health.Conclusions: Successful implementation of precision prevention and epidemiology ini-tiatives requires development of a researcher and practitioner workforce that is well-versed in informatics and public health. The positive impact of precision healthcare ap-proaches depends on solutions and technologies that connect digital patient information with wearable devices, mobile apps, telehealth, and digital analytics using AI. The vital components required to successfully integrate public health informatics, precision pre-vention and epidemiology are people, data, and tool systems, albeit within legal and ethical constraints. Together, these applications can significantly improve actionability of public health surveillance and societal trends in the preservation of health and disease prevention.
Keywords: Clinicogenomics; Digital Informatics; Precision Prevention; Epidemiology; Public Health Informatics; Social Determinants of Health; Surveillance; Telehealth